Wagner's Lohengrin (Opera Journeys Mini Guide Series). - Fisher, Burton D. (Opera Journeys Pub., 2006)
A comprehensive guide to Wagner's LOHENGRIN, featuring Principal Characters in the opera, Brief Story Synopsis, Story Narrative with Music Highlight Examples, and an insightful and in depth Commentary and Analysis by Burton D. Fisher, noted opera author and lecturer.